Evaluation of Quality of Underground Irrigation Water along the Distance from Coastal Line of Northern Saurashtra Region of Gujarat - Kiran Yadav (Journal of the Indian Society of Soil Science, 2023)
Salinity in coastal groundwater is a widespread problem in many parts of India and Gujarat. The coastal tract of Saurashtra is about 850 km in Gujarat. Most of the ground water aquifers situated along the shoreline has been deteriorated by sea water intrusion. The rapidly growing population in India has too necessarily depends on ground water resources for its requirement and altering application of heavy dependency of ground water resources are lowering of water-table and consequent drying has forced the farmer of deepening the wells. The current study aimed to study the quality of underground water of northern coastal region of Saurashtra (Jamnagar, Devbhumi Dwarka and Porbandar district) of Gujarat. In this field-laboratory investigation during 2019-2021, different talukas of northern coastal region of Saurashtra were surveyed twice i.e. pre-monsoon (May, 2019) and post-monsoon (December, 2019). Altogether 285 sampling localities were selected based on geographical situation, climate and local data. In the laboratory, the collected samples were analyzed for electrical conductivity (EC), pH and various indices viz., sodium adsorption ratio (SAR) and SSP. On the basis of analyzed data, it can be concluded that quality of almost all pre-monsoon irrigation water samples were found saline (EC 0.75 dS m-1 and above). The EC values were ranged from 0.25 to 7.35 dS m-1. After monsoon, the EC values were ranged from 0.18 to 6.83 dS m-1. However, all the quality parameters viz., EC, pH, SAR and SSP of collected water samples after monsoon were improved as compared to the samples collected before monsoon.